Correlation of neutrophil ratio to lymphocyte levels before therapy with the incidence of metastasis, lymph node involvements, in urothelial type muscle invasive bladder cancer in Indonesia - Rudi Rafian; Ahmad Zulfan Hendri; Indrawarman Soerohardjo; Raden Danarto (Universitas Gadjah Mada, 2022)
Bladder cancer is cancer originated from the bladder mucosa or urothelium. Bladder cancer is the 9th most common malignancy worldwide and the most common malignancy of the urinary tract. Studies show that cancer triggers an inflammatory response, which causes changes in circulating inflammatory cells. Examination of neutrophils and lymphocytes is an inexpensive examination, reproducible, and easily obtained. Neutrophil to lymphocyte ratio (NLR) values have been used in several studies to evaluate the inflammatory response that occurs in tumors. In urology, the importance of NLR has been recognized in predicting progression and aggressiveness in urothelial bladder tumors, kidney cancer (RCC/renal cell carcinoma), and upper tract urothelial carcinoma (UTUC). This study was a cross-sectional study obtained retrospectively by evaluating the medical records of patients diagnosed with muscle-invasive bladder cancer (MIBC) at Dr. Sardjito General Hospital, Yogyakarta, Indonesia from January 2017 to December 2019. The NLR data were categorized into NLR < 2.5 and > 2.5. As much as 150 patients with bladder cancer were included in this study, with a mean age of 56.43 ± 13.60 years. In the comparison of NLR values and the incidence of metastasis, there were 15 people (20%) with NLR values < 2.5 who had metastasis while 32 people (42.7%) from the group with NLR > 2.5 had metastasis (p = 0.003). In the comparison of NLR values and nodule involvement, there were 25 (33.3%) patients with NLR < 2.5 and 39 (52%) patients with NLR > 2.5 (p = 0.021). This study showed that patients with metastatic bladder tumors and lymph node involvement had a significantly higher NLR value. It can be concluded the NLR value can be used to predict the metastatic level and lymph node involvement in patients with bladder tumors. Even though it is not a specific marker of inflammation, the NLR examination is simple, affordable, easy to obtain, and widely available.